Identification of maturity-onset diabetes of the young through targeted next-generation sequencing in Thai patients with atypical diabetes in real-world practice - Thewjitcharoen, Yotsapon; Chatchomchuan, Waralee; Wanothayaroj, Ekgaluck; Nakasatien, Soontaree; Lim, Cadmon K. P.; Himathongkam, Thep; Chan, Juliana C. N. (Frontiers in Endocrinology, 2026)
IntroductionMaturity-onset diabetes of the young (MODY) is often misdiagnosed as either autoimmune type 1 diabetes (T1D) or polygenic type 2 diabetes (T2D), resulting in missed diagnosis and inappropriate treatment. Differentiating MODY from T2D is challenging in Asians with low body mass index (BMI) and strong family history. The clinical impact of genetic testing in a real-world case series of Thai patients with atypical diabetes is not well defined. In this study, we aim to evaluate the diagnostic yield and clinical implications of targeted gene panel testing at a specialized diabetes outpatient clinic in Bangkok.Materials and methodsWe performed next-generation sequencing analysis of 33 monogenic diabetes genes in Thai patients recruited in 2019–2025 who had atypical features of diabetes including age-at-diagnosis≤ 40 years, BMI ≤25 kg/m2, random plasma C-peptide levels ≥ 0.1 ng/mL after at least three years of clinically-diagnosed T1D, syndromic features such as organ abnormalities or non-classical T1D or T2D presentations.ResultsOf the 33 probands with atypical diabetes (age-at-diagnosis 34.4 ± 14.4 years, BMI 23.7 ± 3.3 kg/m2, insulin-treated 39.3%), genetic testing identified a pathogenic or likely pathogenic variant in 4 (12.1%) probands. Variants in GCK were the most frequent (n=2, 50.0%), followed by HNF1A (n=1, 25.0%), and HNF1B (n=1, 25.0%). Genetic diagnoses led to targeted therapies and identification of MODY cases among family members. The latter often have concomitant obesity-driven insulin resistance contributing to hyperglycemia.ConclusionGenetic testing for monogenic diabetes in a real-world setting identified disease-causing variant in 12.1% of young Thai patients with atypical diabetes. Despite this low yield, accurate genetic diagnoses improved clinical management in both probands and family members. These findings underscore the potential contribution of a strong polygenic background or yet unidentified MODY-X genes among Thai patients. Establishing a register of family-based cohorts documenting the molecular diagnosis of atypical diabetes will advance diagnosis and treatment.